1991
DOI: 10.1002/path.1711630105
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological grading of soft tissue tumours. Prognostic significance in a prospective study of 278 consecutive cases

Abstract: A consecutive 10-year series of 278 soft tissue sarcomas was prospectively graded, using a system based on the number of mitoses and taking into account parameters such as cellularity, anaplasia, necrosis, and histogenetic type and subtype of tumour. Prognostic factors in relation to metastasis-free survival were studied by uni- and multivariate analysis. Fifty-seven (20.5 per cent) were low-grade tumours, 43 (15.5 per cent) were intermediate, and 178 (64 per cent) were high grade. High-grade tumours were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Histopathological grade is a classical prognostic indicator for survival in STS (Jensen et al, 1991;Vraa et al, 1998). We found that all 6 patients with grade I or II tumours were alive and 5 of those had less hypoxic tumours.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Histopathological grade is a classical prognostic indicator for survival in STS (Jensen et al, 1991;Vraa et al, 1998). We found that all 6 patients with grade I or II tumours were alive and 5 of those had less hypoxic tumours.…”
Section: Discussionmentioning
confidence: 62%
“…Based on examinations of biopsy and/or surgical specimens the group pathologist determined the histopathological diagnosis and tumour grade as previously described (Jensen et al, 1991).…”
mentioning
confidence: 99%
“…Five-year survival is highly dependent on the tumor grade. Results varied from 95% for Grade 1, 86% for Grade 2, and 50% for Grade 3 tumors in a series by Jensen et al 33 The value of systemic chemotherapy in these tumors is not yet definitely known, its role being limited to those patients with a poor prognosis including large tumor size, high grade, or metastatic disease. …”
Section: Discussionmentioning
confidence: 95%
“…31P-MRS and PO, assessment were done immediately after the routine magnetic resonance imaging (MRI). Between 1 and 7 days later (median 2 days) a biopsy was excised (or the entire tumour surgically removed) and histopathological diagnosis was achieved (17). This revealed that 27 tumours were soft tissue sarcomas, of which 2 were recurrent diseases.…”
Section: Patientsmentioning
confidence: 99%